Foto(eletro)reforma do glicerol empregando filmes de Bi2WO6 como fotoanodos seletivos - Nascimento, Lucas Leão (2021)
The growing demand for energy by the modern society has intensified the search for alternative energy sources. In this way, the use of biofuels has increased dramatically in recent decades, which led to the co-production of glycerol far above what the current market capability. In this context, the reform of glycerol is important, both for the possibility of obtaining high value compounds in addition to H2 production, and for the associated environmental benefits. Hence, the present work aimed to investigate Bi2WO6 as a photocatalyst for the selective oxidation of glycerol, with concomitant H2 evolution. Nano Bi2WO6 was synthesized by the hydrothermal method under different pH conditions. The materials were evaluated in terms of the photocatalytic performance by methanol photoreform, so that the Bi2WO6 obtained at pH = 0 exhibited the best results and, therefore, was chosen for the further experiments. The powder was then immobilized on conductive vitreous substrates using the Doctor Blade technique. The films obtained were used as photoanodes and evaluated against photoelectrocatalytic reforming of glycerol. The devices based on Bi2WO6 photoanodes reached an H2 production of 20.0 µmol h-1 cm-1 from 10% v/v glycerol solutions at 0.8 V vs Ag/AgCl, while the devices formed by TiO2 P25 photoanodes produced 5,3 µmol h-1 cm-1 at the same conditions. Bi2WO6 photoanodes exhibited photoresponse up to 420 nm with maximum incident-light to current efficiency of 53% at 330 nm. When photoelectrochemical cells containing the Bi2WO6 photoanodes were submitted to UV-Vis irradiation (120 mW cm-2) for 6 h and 0.8 V vs Ag/AgCl external bias, a conversion of 43% of glycerol was achieved with 88% selectivity towards formic acid production in 0.1M aqueous K2SO4 solution containing 10% v/v of glycerol with pH = 3.6. At pH = 6.4, 65% conversion with 41% of selectivity to formic acid formation was achieved. In both cases, the faradaic efficiency for the production of H2 was 100%. The results confirmed the Bi2WO6 thin films can be successfully applied in the solar energy conversion to fuels with simultaneous valorization of biomass derivatives.